The effect of high fat diet and metformin treatment on liver lipids accumulation and their impact on insulin action - Piotr Zabielski (Nature Portfolio, 2018)
Abstract We sought to determine whether metformin treatment reverses a high-fat diet (HFD)-induced hepatic insulin resistance (IRes) and to identify lipid intermediates involved in induction of liver IRes. The experiments were conducted on male Wistar rats divided into three groups: 1. Control, 2. fed HFD and 3. fed HFD and treated with metformin. The animals were infused with a [U-13C]palmitate to measure fractional lipid synthesis rate. This allowed for the calculation of fractional synthesis rate of signaling lipids (FSR) through the estimation of their isotopic enrichment. Liver ceramide (Cer), diacylglycerol (DAG) and acyl-carnitine concentration and enrichment were analyzed by LC/MS/MS. The content of proteins involved in lipid metabolism and insulin signaling were analyzed by Western Blot. HFD treatment increased the content and FSR of DAG and Cer in the liver which was accompanied by systemic insulin resistance and inhibition of hepatic insulin signaling pathway under insulin stimulation. Metformin treatment ameliorated systemic insulin resistance and augmented the hepatic insulin signaling cascade. It reduced both the concentration and FSR of Cer, DAG, and increased acyl-carnitine content and the expression of mitochondrial markers. We postulate, that in liver, the insulin sensitizing effect of metformin depends on augmentation of mitochondrial β-oxidation, which protects from hepatic accumulation of both the Cer and DAG and preserves insulin sensitivity under HFD consumption. Moreover, we showed that hepatic content of Cer and DAG corresponds with their respective FSR.